Laboratorium Study of Asphalt Starbit E-55 Polymer Modified Application on Asphalt Concrete Wearing Course (Ac-Wc) - Damianus Kans Pangaraya (Journal of the Civil Engineering Forum, 2015)
The conventional asphalt road has almost been considered fail to serve the transportation needs. It is indicated by the occurrence of premature damage which is caused by vehicle load and climate. Starbit E-55, the polymer modified bitumen, is formulated to meet the requirement of transport development. Considering those needs, it is important to investigate the feasibility level of that modified bitumen as alternate asphalt instead of the conventional one. This research began with the measurement of the properties of hard layered AC-WC Starbit E-55, then comparing the result to 60/70 penetration of Pertamina asphalt. The next step is then, to determine the converted value so as to be close to that of Pertamina (60/70 penetration). This step is conducted by applying durability and ITS tests on the mixture. Result of the tests showed that hard layered AC-WC Starbit E-55 has better characteristic at 5.7% optimum level asphalt and 6.4% of Pertamina asphalt (60/70 penetration). Starbit E-55 converted level within hard-layered ACWC is 5.6%. The performance test result on immersion with variance of 1, 3, 5, 7 and 14 days shows that durability value of Starbit E-55 AC-WC has better performance. During the process, Starbit E-55 required 15.38% higher energy consumption.